Enhanced electrical properties by tuning the phase morphology of multiwalled carbon nanotube‐filled poly(ether ether ketone)/polyimide composites. Issue 6 (13th March 2015) - Gao, Cong; Han, Bing; Zhang, Shuling; Pang, Jinhui; Wang, Guibin; Jiang, Zhenhua
<x xml:space="preserve">Abstract</x> Enhanced electrical properties of poly(ether ether ketone)/thermoplastic polyimide/multiwalled carbon nanotube composites were achieved using the concept of double percolation.